2015
DOI: 10.1002/jcph.563
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐ and transporter‐mediated beverage–drug interactions: An update on fruit juices and green tea

Abstract: Beverage-drug interactions have remained an active area of research and have been the subject of extensive investigations in the past 2 decades. The known mechanisms of clinically relevant beverage-drug interactions include modulation of the activity of cytochrome P450 (CYP) 3A and organic anion-transporting polypeptide (OATP). For CYP3A-mediated beverage-drug interaction, the in vivo CYP3A inhibitory effect is limited to grapefruit juice (GFJ), which increases the bioavailability of several orally administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 144 publications
(471 reference statements)
0
38
0
Order By: Relevance
“…Grapefruit ( Citrus paradisi ) juice is known for its ability to alter drug metabolism through inhibition of cytochrome P450‐3A4 and results in drug–food interactions that may be life threatening (An et al ., ). The primary active ingredients in Citrus responsible for these effects are the furanocoumarins bergapten, bergamottin, and 6′,7′‐dihydroxybergamottin (Guo et al ., ; Paine et al ., ; Fujita et al ., ; Messer et al ., ; Greenblatt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Grapefruit ( Citrus paradisi ) juice is known for its ability to alter drug metabolism through inhibition of cytochrome P450‐3A4 and results in drug–food interactions that may be life threatening (An et al ., ). The primary active ingredients in Citrus responsible for these effects are the furanocoumarins bergapten, bergamottin, and 6′,7′‐dihydroxybergamottin (Guo et al ., ; Paine et al ., ; Fujita et al ., ; Messer et al ., ; Greenblatt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This was amply demonstrated in an early study in rabbits by Pineau et al (1991) which revealed large increases in CYP3A6 expression and activity associated with switch of diet from breast milk to solid diets at weaning. Subsequently, many investigators have focused on the CYP-regulatory effects of specific dietary components including dietary fats (reviewed by Hardwick et al, 2009); ethanol (reviewed by Ingelman-Sundberg et al, 1994; Ronis et al, 1996; Li and Cederbaum 2008) and phytochemicals in fruits and vegetables (reviewed by Ioannides, 1999; Lamps and Petersen, 2002; Murray 2006; Rodriguez-Fragoso et al, 2011; An et al 2015). In addition, a significant amount of work has examined the effects of dietary protein composition, in particular soy protein and its associated phytochemicals, on CYP expression and activity.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit juice (GFJ, OJ, and OJ) inhibition of the organic anion‐transporting polypeptides (influx transporter at the intestinal and hepatic levels) also led to significant drug interactions. Interactions of fruit juices with P‐gp have also been reported, but the effect is minimal with no evidence of clinically relevant interactions . Very recently, inhibition of fruit juices and green tea on BCRP has been demonstrated in vitro with dasatinib as a dual substrate of P‐gp and BCRP .…”
Section: First‐pass Effect Of Tkismentioning
confidence: 99%